Pengaruh Rasio Keuangan terhadap Pertumbuhan Laba pada Perusahaan Sub Sektor Makanan dan Minuman yang Terdaftar di Bursa Efek Indonesia Periode 2020-2022 - Sipahutar, Cinta Ruth; Gaol, Manatap Berliana Lumban; Siboro, Danri Toni (AKADEMIK: Jurnal Mahasiswa Ekonomi & Bisnis, 2024)
This study aims to determine the effect of financial ratios on profit growth in food and beverage sub-sector companies listed on the Indonesia Stock Exchange in 2020-2022. The dependent variable in this study is profit growth, the independent variables in this study are Return On Asset, Net Profit Margin, Current Ratio, Debt to Asset Ratio and Total Asset Turnover. The population in this study was 84 companies and the sample used was 30 companies with purposive sampling techniques. The data used in this study is secondary data sourced from the company's financial statements and annual reports. The research method used in this study is quantitative research with multiple linear regression analysis techniques and data processing using the SPSS program version 25. The results of this study show that NPM has a positive and significant effect on profit growth. ROA and CR have a negative and significant effect on profit growth. DAR has a negative and insignificant effect on profit growth, while TATO has a positive and insignificant effect on profit growth.